2015
DOI: 10.1055/s-0035-1562879
|View full text |Cite
|
Sign up to set email alerts
|

An Inferiorly Based Rotation Flap for Defects Involving the Lower Eyelid and Medial Cheek

Abstract: We report a series of 20 patients who underwent inferiorly based rotation flaps for reconstruction of defects of the medial and infraorbital cheek and lower eyelid following Mohs micrographic surgery for nonmelanoma skin cancer. Defects ranged from 1.2 to 3.2 cm in longest diameter and patients ranged from 27 to 91 years of age. All 20 patients had excellent functional and cosmetic outcome with up to 2-year follow-up and no subsequent surgical or laser revision. There were no instances of partial or complete f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Past reports have discussed this repair approach for defects smaller than 3.2 to 3.4 cm in longest diameter. 5,6 In this series, defects up to 5.5 cm were successfully repaired with an inferiorly based flap with acceptable cosmetic outcomes based on the VAS.…”
Section: Discussionmentioning
confidence: 92%
“…Past reports have discussed this repair approach for defects smaller than 3.2 to 3.4 cm in longest diameter. 5,6 In this series, defects up to 5.5 cm were successfully repaired with an inferiorly based flap with acceptable cosmetic outcomes based on the VAS.…”
Section: Discussionmentioning
confidence: 92%
“…[12] In addition, the pedicle of this flap should be inferior-based rather than lateral-based to prevent postoperative lid retraction. [11] Postoperative anthropometric measurements of this flap showed that poor design can cause a significantly increased risk of lower lid distortion, and therefore careful design must be performed to apply techniques that prevent lower lid retraction. [12] To prevent cheek sagging and ectropion, suturing the undersurface of the flap to the malar periosteum is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The cheek is undermined widely in the superficial to midsubcutaneous level to ensure adequate flap mobilization and eliminate tension along closure lines. 4,8,12 The flap is advanced medially to close the defect and one to three sutures are placed from the undersurface of the flap to the periosteum of the ascending process of the maxilla in the nasofacial junction using absorbable 4-0 suture material (Biosyn, glycolide/dioxanone/trimethylene polyester [Medtronic USA, Minneapolis, MN] or Vicryl, polyglactin 910 [Ethicon, Inc., Bridgewater, NJ]). The periosteal suture is placed first to maintain concavity of the nasofacial sulcus, relieve tension along the flap, and eliminate dead space.…”
Section: Techniquementioning
confidence: 99%
“…The periosteal suture is placed first to maintain concavity of the nasofacial sulcus, relieve tension along the flap, and eliminate dead space. 4 Once in place, the flap can be trimmed to allow for approximation of all wound edges. For the reminder of the flap and standing cone defects, absorbable 5-0 polyglactin 910 buried deep dermal sutures are placed to approximate the dermis and absorb maximal tension along the suture line.…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation